Let the data be $(y_i , X_i) $ where $y_i$ is real valued and $X_i$ is a q-vector.

The regression function for $y_i$ on $X_i$ is $g(x) = E(y_i | X_i = x)$, we can write this as: $$y_i = g(X_i) + e_i$$ where $E(e_i | X_i ) = 0$.

Now since $E(e_i | X_i ) = 0$ then it follows that $E(k(\frac{X_i - x}{h})e_i) = 0$

where $k$ is a kernel function. What is the reason of this implication?


If $X_i$ is known, then this implies that the function $k\left(\frac{X_i - x}{h}\right)$ is known. In other words we have that for the conditional expectation:

$$ \operatorname{E}\left( k\left(\frac{X_i - x}{h} \right) e_i \mid X_i \right) = k\left(\frac{X_i - x}{h}\right) \operatorname{E}(e_i \mid X_i)=0 $$

Therefore, we have by the law of iterated expectations that:

$$ \operatorname{E}\left( k\left(\frac{X_i - x}{h} \right) e_i \right) = \operatorname{E}\left( \operatorname{E}\left(k\Big(\frac{X_i - x}{h}\Big) e_i \mid X_i \right) \right) = \mathrm{E}(0) = 0 $$

as required.


$E(k(\frac{X_{i} - x}{h})e_{i}) = E(E(k(\frac{X_{i} - x}{h})e_{i}|X_{i}))$ by tower property

$= E(k(\frac{X_{i} - x}{h})E(e_{i}|X_{i}))$ because $k(.)$ is deterministic given $Xi$

$=E(k(\frac{X_{i} - x}{h})0)=0$ since $E(e_{i}|X_{i})=0$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.